Home Schooling and the Future Labor Market-Is There an Adequate Educational Answer for the Extensive Changes in the Labor Market? - Oz Guterman; Ari Neuman; Efrat Gill (MDPI AG, 2024)
Various aspects of human existence are changing, and these changes are having a significant effect on the current and future labor market. Some occupations are estimated to be at high risk of disappearing over the next several decades, others are at medium risk, while some are at low risk. At the same time, new trades are emerging. In order to successfully cope in an era where changes occur so frequently and so rapidly, and to be a part of the current and future labor market, we need to utilize a certain set of skills and competencies that is often referred to as "21st century skills". This opinion paper argues that homeschooling is an education path that takes into account the extensive rapid changes in the 21st century as well as in the labor market and strives to give children the skills and competencies to cope with them successfully.